Measured methods for protecting computer network against computer virus - Leiyawor, Asase Jesse (Національний університет «Львівська політехніка», 2022)
Context: Since the creation of the computer, there has been a rapid increase in computer viruses from the past years. With the increasing number of computers resorting to the use of software, there is a necessity of keeping data of various users using different ways. Some significant difficulties that Computer Networks are facing are securing, protecting, and processing the data, which is the user's property. Aims and Objective: The main goal of this research is to know and understand the security threats and recognize the appropriate security methods that will be used to prevent computer viruses. The main objectives of this research are: • To recognize the security issues and the techniques used in the expansion of computer viruses in the current world of computer networks. • To pinpoint the security challenges and those that are expected in the future of computer networks • To indicate countermeasures for the future challenges to be countered in computer networks Research Methodology: In this study, we have used two exploring methods; • Survey and evaluation with various users of computer networks • Systematic Literature Review. Conclusion: The identification of security challenges and preventive the approach to computer viruses is a very challenging task. In the procedure of discovery from research methods (SLR and Survey), we had pinpointed an adequate number of challenges and preventive approaches used at present and so in future computer networks.
Keywords: Challenges, Computer Virus, Security, Techniques